Prevalence of Strabismus among Patients Attending Basrah Teaching Hospital, Basrah, Iraq - Mohammed Al Ashoor; Hamid Al Taha (Al-Anbar Medical Journal)
Background: Strabismus is a relatively widespread disorder. However, there is no local relevant study examined its prevalence.Objectives: To measure the prevalence and types of strabismus.Materials and methods: The study was a hospital-based cross-sectional study involving 10257 participants. Each participant underwent comprehensive ophthalmological examinations to assess strabismus, evident through their various characteristics. The patients were divided into two main groups: Concomitant and incomitant groups. Detailed data regarding the demographic (age, sex, age at presentation, and family history of strabismus) as well as the presence of amblyopia and diplopia were registered for every patient.Results: Of 10257 participants, 6836 (66.6%) were male. The patients ranged in age from 4 months to 57 years, with a mean age of 1.68 years. The prevalence rate of strabismus was 6.5%. Esotropia (52.9%) was more prevalent than other types of strabismus. Strabismus was more common in ages under ten years old and in the ages of presentation under ten years old. There were no statistically significant differences (P- value > 0.05) between these two variables and strabismus. While male sex was significantly associated with a higher prevalence rate of strabismus (P-value = 0.019). A positive family history of strabismus, the presence of amblyopia or diplopia were more common in patients without strabismus than those with strabismus (P- value < 0.05).Conclusions: Strabismus was a common (6.5%) disease. Esotropia was the most common type of strabismus. The study primarily observed strabismus in younger individuals and males, underscoring the significance of early screening in these groups. Contrary to expectations, the study found that having a family history of strabismus, amblyopia, or diplopia does not significantly impact the likelihood of developing it, suggesting that other factors may play a greater role in its prevalence.